2018
DOI: 10.5604/01.3001.0011.7307
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Needle Number on the Heat Insulation Performance of Pre-oxidized Fibre Felts

Abstract: Many factors were needed to be considered to prepare pre-oxidised fibre felts with excellent heat insulation performance, and different production processes showed differences in the heat insulation performance of pre-oxidised fibre felts. In order to probe into the influence of the production process on the heat insulation performance of materials, a large number of experiments were needed to be carried out. For needle-punched nonwoven pre-oxidised fibre felts, web features, needle characteristics and the nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…These results correlate well with the results obtained by µCT analysis. A similar effect has been observed in previous studies [ 64 , 65 , 66 ], which confirmed the influence of needle-punching density on thermal conductivity by producing a series of CFs with different needle-punching densities. Therefore, the combined effects of the conductive nature and orientation of the carbon fibers influences the anisotropic heat transfer behavior.…”
Section: Resultssupporting
confidence: 91%
“…These results correlate well with the results obtained by µCT analysis. A similar effect has been observed in previous studies [ 64 , 65 , 66 ], which confirmed the influence of needle-punching density on thermal conductivity by producing a series of CFs with different needle-punching densities. Therefore, the combined effects of the conductive nature and orientation of the carbon fibers influences the anisotropic heat transfer behavior.…”
Section: Resultssupporting
confidence: 91%